Optimización de Tutores Inteligentes mediante la Teoría de Respuesta al Reactivo y Lógica Difusa para la Personalización de Contenidos Educativos - Chávez-Vega, N.B.; Cazarez-Castro, N.R.; Luviano-Cruz, D. (RIIIT Revista Internacional de Investigación e Innovación Tecnológica, 2025)
Currently, there is a growing interest in developing intelligent tutors that, through the recommendation of various educational materials, can have a positive impact on the learning process of students. In order to personalize the content presented by these tutors, techniques such as behaviour analysis, interests, and study habits, among others, have been used. However, the inclusion of crucial factors such as the cognitive ability of the student and the level of difficulty of the educational material provided by the tutor has been overlooked. This omission of fundamental aspects can lead to an excessive burden and disorientation for the student, resulting in a lack of interest in using the tutor. For this reason, this work proposes the application of Reactive Response Theory to determine the difficulty of exercises, along with the implementation of a fuzzy system to define the current ability of the student.